2018
DOI: 10.1590/s0102-053620180411
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-efficiency phosphorus fertilizer: promising technology for carrot crop

Abstract: Several studies were carried out to evaluate polymer-coated mineral fertilizers; however, few studies, on the agronomic efficiency of these fertilizers in the field in carrot crop, are available. Thus, we aimed to evaluate the use of enhanced-efficiency phosphorus fertilizer coated with polymers in carrot (Daucus carota). The experiment was carried out in field, in Ipameri-GO. The experimental design was randomized blocks, arranged in an incomplete factorial design (5x2)+1, considering five phosphorus doses (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…The combined application of plant residues with phosphate fertilization promoted higher production of fresh matter of marketable roots and also reduced mass losses during storage (Araújo et al 2004). Pelá et al (2018) observed increments in plant height, root length and yield of carrot, in addition to the improvement in commercial standards of roots with the use of phosphate fertilizer.…”
Section: Introductionmentioning
confidence: 87%
“…The combined application of plant residues with phosphate fertilization promoted higher production of fresh matter of marketable roots and also reduced mass losses during storage (Araújo et al 2004). Pelá et al (2018) observed increments in plant height, root length and yield of carrot, in addition to the improvement in commercial standards of roots with the use of phosphate fertilizer.…”
Section: Introductionmentioning
confidence: 87%
“…A similar strategy could be applied with additives of iron and aluminum affinity, elements responsible for P fixation in the soil because it's possible to increase fertilizer agronomic efficiency by using these additives to cover it. Increasing P fertilizer efficiency with P fertilizer coated with anionic polymers (Policote) was demonstrated P by Reis Jr and Silva (2012), Chagas et al (2015), Chagas et al (2016), Chagas et al (2017), Guelfi et al (2018), Pelá et al (2018), Pelá et al (2019), and Zanão et al (2020).…”
Section: Introductionmentioning
confidence: 95%
“…Nitrogen makes up many of the components of plant cells, such as amino acids, amides, proteins, nucleic acids, among others (Oliveira et al, 2014). Phosphorus is essential for their establishment and development (Pelá et al, 2018). It favors the root system, increasing the absorption of water and nutrients, resulting in increased yield (Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in irrigation and fertilization analyzed in isolation (Silva et al, 2015;Akhmedov et al, 2018;Carvalho et al, 2018;Pelá et al, 2018) contribute to gains in the production of the carrot crop. However, there is little information about the evaluation of these factors of production in a combined way and their contributions to the increase in production in an economical way.…”
Section: Introductionmentioning
confidence: 99%